2014
DOI: 10.1038/bjc.2014.454
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1246 expression associated with CCNG2-mediated chemoresistance and stemness in pancreatic cancer

Abstract: Background:Pancreatic cancer has a poor prognosis because of its high refractoriness to chemotherapy and tumour recurrence, and these properties have been attributed to cancer stem cells (CSCs). MicroRNA (miRNA) regulates various molecular mechanisms of cancer progression associated with CSCs. This study aimed to identify the candidate miRNA and to characterise the clinical significance.Methods:We established gemcitabine-resistant Panc1 cells, and induced CSC-like properties through sphere formation. Candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 25 publications
8
103
0
3
Order By: Relevance
“…In gastric cancer, CCNG2 expression correlates with the extent of differentiation: CCNG2 expression is high in well-differentiated adenocarcinomas and low in poorly-differentiated adenocarcinomas (12). In our previous study, CCNG2 induced apoptosis and was partially associated with cancer stemness in a pancreatic cancer cell line (13). In summary, CCNG2 is heavily involved in cancer progression, including proliferation, invasion, chemoresistance and differentiation in various cancer types.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In gastric cancer, CCNG2 expression correlates with the extent of differentiation: CCNG2 expression is high in well-differentiated adenocarcinomas and low in poorly-differentiated adenocarcinomas (12). In our previous study, CCNG2 induced apoptosis and was partially associated with cancer stemness in a pancreatic cancer cell line (13). In summary, CCNG2 is heavily involved in cancer progression, including proliferation, invasion, chemoresistance and differentiation in various cancer types.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have reported that CCNG2 is involved in a variety of functions associated with cancer progression, including the regulation of cell proliferation (8-10), chemoresistance (8), DNA repair (11) and cell differentiation (12). Furthermore, our previous study demonstrated that CCNG2 was associated with chemoresistance and cancer stemness via cell apoptosis in pancreatic cancer (13). Recently, CCNG2 has been reported as a novel prognostic marker in several types of cancer (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…miRs regulate the gene expression in the majority of biological processes in the cell, and therefore have been hypothesized to serve an important role in the chemoresistance to standard treatment regimens in pancreatic cancer. Numerous studies demonstrated that miRs are differentially expressed in a variety of types of cancer (44)(45)(46)(47)(48)(49)(50). A study examining the miR profile of gemcitabine-sensitive and resistant pancreatic cancer cell lines reported the presence of 33 differentially regulated miRs (44).…”
Section: Pancreatic Stellate Cells (Pscs)mentioning
confidence: 99%
“…Another study demonstrated that miR-21 overexpression results in an increased sensitivity to gemcitabine via a decrease in the expression levels of the p85α subunit of phosphatidylinositol-4,5-biphostphate 3-kinase (47). miR-1246 has been revealed to increase stemness and induce drug resistance in pancreatic cancer cell lines (48). Similarly, miR-221/222 was demonstrated to induce pancreatic cancer progression through the regulation of MMPs (49), indicating that miRs may be pro-and anti-oncogenic.…”
Section: Pancreatic Stellate Cells (Pscs)mentioning
confidence: 99%